Delivering multi-dimensional da’wah in digital space: Experience from Gita Wirjawan’s YouTube channel - A'yun, Fathimah Nadia Qurrota; ‘Ubudiyah, Farikhatul (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
The development of da'wah into the digital realm, especially through platforms such as YouTube, demands a multidimensional message, going beyond traditional ritual and legal aspects to include social, educational, economic, and cultural issues. This study aims to analyse the dimensions of the da'wah message contained in the content of Gita Wirjawan's YouTube channel, which implicitly conveys multidimensional good values. Using a qualitative approach with deductive content analysis on three selected podcast videos from 2025, this study identifies and interprets the multidimensional da'wah themes presented. The results of the analysis reveal that Gita Wirjawan's YouTube content implicitly contains multidimensional da'wah messages classified in aspects of theology, sharia, and muamalah principles, and Islamic ethics, which are discussed through dialogues with expert speakers on issues of faith, social justice, meritocracy, and human resource development. The findings have implications for the need for a strategic, interdisciplinary, and moderate digital da'wah approach, and highlight the crucial role of content creators and various elements of society in inclusively disseminating transformative Islamic values. ***** Perkembangan dakwah ke ranah digital, khususnya melalui platform seperti YouTube, menuntut adanya pesan yang multidimensi, melampaui aspek ritual dan hukum tradisional untuk mencakup isu sosial, pendidikan, ekonomi, dan budaya. Penelitian ini bertujuan untuk menganalisis dimensi-dimensi pesan dakwah yang terdapat pada konten kanal YouTube Gita Wirjawan, yang secara implisit menyampaikan nilai-nilai kebaikan secara multidimensi. Menggunakan pendekatan kualitatif dengan analisis konten deduktif pada tiga video podcast terpilih dari tahun 2025, studi ini mengidentifikasi dan menginterpretasikan tema-tema dakwah multidimensional yang disajikan. Hasil analisis mengungkapkan bahwa konten YouTube Gita Wirjawan secara implisit mengandung pesan dakwah multidimensi yang terklasifikasi dalam aspek teologi, syariah dan prinsip muamalah, serta etika Islam, yang dibahas melalui dialog dengan narasumber ahli mengenai isu-isu keimanan, keadilan sosial, meritokrasi, dan pengembangan sumber daya manusia. Temuan ini berimplikasi pada perlunya pendekatan dakwah digital yang strategis, interdisipliner, dan moderat, serta menyoroti peran krusial kreator konten dan berbagai elemen masyarakat dalam menyebarluaskan nilai-nilai Islam yang transformatif secara inklusif.